EFFECTIVENESS OF ARABICA COFFEE PLANT PRUNING TECHNIQUES (Arabica Coffea) - Yudi Siswanto; Isnar Sumartono; Andi Setiawan; Nadia O. Simamora (Yayasan Sinergi Multidimensi Kreatif, 2025)
Effectiveness of Arabica Coffee Plant Pruning Technique (Coffea arabica) The purpose of this study was to determine the effectiveness of Arabica coffee plant pruning techniques (Coffea arabik). This study was conducted from April to June 2025 in Aeksabaon Village, Marancar District, South Tapanuli Regency, North Sumatra Province. The altitude is ± 75 meters above sea level. The study used the Non-Factorial Randomized Block Design (RAK) method with treatment factors. N1 = Form Pruning, N2 = Production Pruning, N3 = Rejuvenation Pruning. The research parameters include; wet fruit production per sample (g), wet fruit production per plot (g), dry fruit production per sample (g), dry fruit production per plot (g), dry bean production per sample (g), dry bean production per plot (g), weight of 100 dry beans (g). The results of the study showed that the effectiveness of pruning had a significant effect on the production of fresh fruit per sample (g), production of wet fruit per plot (g), production of dry fruit per sample (g), production of dry fruit per plot (g), production of dry seeds per sample (g), production of dry seeds per plot (g), and weight of 100 dry seeds (g).